The Global Economic Crisis Reflected in the Statistical Forecasts : Array - Ionescu, Romeo-Victor (EuroEconomica, 2020)
The research is focused on the idea that good statistical data are able to support a correct economic analysis even under pandemic’s impact. The main objective of the research is to point out the statistics’ possibilities to adapt to an uncertain global economic environment. On the other hand, the comparative analysis allows to realize the new world economic top and to nominalize the winner and the looser of these new conditions.